Anti-insulin-like growth factor-IIP3 DNAzymes inhibit cell proliferation and induce caspase-dependent apoptosis in human hepatocarcinoma cell lines - Zhang M; Drummen GPC; Luo S (Dove Medical Press, 2013)
Min Zhang,1 Gregor PC Drummen,2 Su Luo11Medical Department, Beihua University, Jilin, People's Republic of China; 2Cellular Stress and Ageing Program, Bionanoscience and Bio-Imaging Program, Bio & Nano-Solutions, Düsseldorf, GermanyBackground: Insulin-like growth factor II (IGF-II) is a fetal growth protein and an important proangiogenic factor controlled by four promoters (P), of which P2–P4 are inactive in the adult liver. Reactivation and dysregulation of IGF-IIP3 in particular is associated with the attenuation of apoptosis and increased proliferation in a number of liver cancer cell types. Its involvement in experimental liver carcinogenesis makes it a potential target for cancer gene therapy. We designed two IGF-IIP3 specific DNAzymes (DRz1 and DRz2) that target IGF-IIP3 messenger RNA (mRNA) with the aim of reducing IGF-II expression through promoter 3.Methods: IGF-IIP3 mRNA and protein expression levels were assessed using real-time polymerase chain reaction and gel electrophoresis/western blotting after transfection with Lipofectamine® in SMMC-7721, Huh7, and HepG2 cell lines. Cell proliferation was determined via MTT assay; apoptosis was evaluated by fluorescence microscopy and with flow cytometry; procaspase-3 and -9 expression were detected via western blotting; and caspase activity was assayed colorimetrically. Standard procedures were used to calculate means and standard deviations, and P-values below 0.05 were considered to indicate significant differences.Results: DRzs were transfected into hepatocellular carcinoma cells and the results showed that DRz1, in particular, could decrease the expression of IGF-IIP3 by nearly 50%. Furthermore, DRz1 significantly inhibited cell proliferation and induced apoptosis. In addition, the downregulation of IGF-IIP3 expression was associated with increased caspase-3 and -9 activity in SMMC-7721 cells after 24 hours of transfection. In all experiments, the efficacy of DRz2 to influence IGF-IIP3 levels and associated effects remained second to DRz1.Conclusion: Overall, these results suggest that DRz1-based targeting of IGF-IIP3 mRNA might have antitumorigenic activity and may potentially provide the basis for a novel therapeutic intervention in liver cancer treatment, although further development is required.Keywords: DNAzymes, proliferation, apoptosis, IGF-II, caspase, hepatocellular carcinoma, cancer